KEPUASAN PASIEN POLIKLINIK PENYAKIT DALAM BERKORELASI DALAM PENERAPAN PROTOKOL KESEHATAN COVID-19 DI SUMATERA BARAT - Mera Delima; Def Primal (Jurnal Cakrawala Ilmiah, 2021)
The implementation of the Covid-19 health protocol is carried out to break the chain of the spread of the Covid-19 virus. The implementation of the Covid-19 health protocol one of which is in the hospital so will affect patient satisfaction. Patient satisfaction is the level of patients’ feelings towards the performance of health services received. This study aims to find out the relationship of the application of protocol health Covid-19 with patient satisfaction in the polyclinic of internal disease, Achmad Darwis Hospital. Research design uses observation sheets for the application of protocol health Covid-19 and patient satisfaction. The study involved 83 respondents. This cross-sectional study obtained analytical observations methods. The research findings had revealed the satisfaction of 70,6% of respondents (p-value ≤ 0,05) which means there is a correlation between the implementation of the Covid-19 health protocol and patient satisfaction along with hospitalization. It can be concluded that the implementation of the Covid-19 protocol health is significantly related to patient satisfaction quality which is protecting patients along the caring process in the hospital.